2012
DOI: 10.1016/j.taap.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver mitochondrial damage under acute or chronic carbon tetrachloride-induced intoxication: Protection by melatonin and cranberry flavonoids

Abstract: In current societies, the risk of toxic liver damage has markedly increased. The aim of the present work was to carry out further research into the mechanism(s) of liver mitochondrial damage induced by acute (0.8 g/kg body weight, single injection) or chronic (1.6 g/ kg body weight, 30 days, biweekly injections) carbon tetrachlorideinduced intoxication and to evaluate the hepatoprotective potential of the antioxidant, melatonin, as well as succinate and cranberry flavonoids in rats. Acute intoxication resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 46 publications
(50 reference statements)
7
36
0
2
Order By: Relevance
“…In fact, there is evidence that mitochondria may have the capacity to synthesize and metabolize MEL [49,50]. It has been demonstrated that MEL pharmacological doses affected the mitochondrial function and prevented mitochondrial dysfunction under pathological conditions [5153]. In addition, a recent paper [54] reported that MEL ability in reducing cell damage seems due to its capacity in decreasing oxidative stress and in stimulating GHS level.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is evidence that mitochondria may have the capacity to synthesize and metabolize MEL [49,50]. It has been demonstrated that MEL pharmacological doses affected the mitochondrial function and prevented mitochondrial dysfunction under pathological conditions [5153]. In addition, a recent paper [54] reported that MEL ability in reducing cell damage seems due to its capacity in decreasing oxidative stress and in stimulating GHS level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the investigation of hepatoprotective activity of foods, medicinal plants and their bioactive constituents is one of the major goals in medical research today. Carbon tetrachloride (CCl 4 )-intoxication is a common animal model for studying the mechanism of liver injury as well as hepatoprotective activity of natural and synthetic compounds [3]. There is increasing evidence to suggest that the antioxidant properties of food phenolics is beneficial to liver health, including protection against chemically-induced hepatotoxicity [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of CCl 4 induced hepatic injury is multifactorial, ranging from inflammation and oxidative stress to immunological and apoptotic reactions. CCl 4 has been shown leading to the loss of antioxidant components such as SOD and CAT [5]. Although, there is great advance in understanding the molecular pathology of liver injury, there have been no effective treatments for the fish hepatobiliary syndrome [6]; hence the search for plant-based remedies is of considerable interest to researchers and aquatic medicine producers.…”
Section: Introductionmentioning
confidence: 99%